Teaching 3-Dimensional Modeling of 2 Concentrations of Substances with Diffusion Reaction System - Situmorang, Astrid Sovana; Ariyanti, Desy Dwi; Nursidiq, Muhamad Syeha (Current STEAM and Education Research, 2024)
This research models the concentration of two substances in three-dimensional space with a reactiondiffusion system. The underlying partial differential equations (PDEs) are solved numerically using the finite difference method. Simulation results show the spatial and temporal variation of the concentrations of the substances, influenced by the diffusion, reaction, and boundary constants. This study introduces an innovative 3-dimensional modeling tool specifically designed to enhance students' understanding of complex diffusion reaction systems. Through the interactive 3-dimensional modeling tool students can observe how these substances diffuse and react over time, offering a dynamic way to explore complex scientific concepts. The result of the research with this tool is that it can significantly improve the learning process by transforming theoretical knowledge into practical, real-world understanding.